Analisis Risiko Proyek KPBU SPAM Regional Wosusokas Provinsi Jawa Tengah - Perspektif Pemerintah - Sutantiningrum, Kartika Hapsari; Utami, Sri Rejeki Laku (Universitas Diponegoro, 2019)
During the dry season there was a scarcity of the availability of clean water in several Central Java province (Wonogiri, Sukoharjo, Karanganyar Disrict and Surakarta City), including Wosusokas Regional Region, so the government often drops clean water. So, the Government conducted the Wosusokas Regional Water Supply System Program. Public-Private Partnership (PPP) scheme is an option to overcome investment cost. This study aims to identify and analyze the risks of Wosusokas regional water supply system project eith government perspective. This research adopted a case study and literature analyze. Selected respondents from PDAB Tirta Utama, Dinas Bina Marga dan Cipta Karya Central Java, BPPW Central Java, District/ City Governments (Regional Water Supply Company, Bappeda and DPU) from Wonogiri, Sukoharjo, Karanganyar and Surakarta. The result found 35 risk factors that could potentially project failure or delay, the majority of these are considered high (11,43%), moderate (54,29%) and low (34,29). Risk factors with high probability are delay and increase cost of land acquisition, failure to complete the contract by the contractor / sub-contractor, failure initial tariff and delay periodic tariff adjustments. The results are useful for Government as a reference in managing the risks of PPP Spam Regional especially in Central Java.